Фауна эктопаразитов в наземных гнездах серых полевок (Microtus Sсhг.) Тувы - Летов, Г.С.; Летова, Г.И. (Вестник зоологии, 1974)
﻿ Species composition of fleas in the terrestrial nests of Microtus (Microtus) oeconomus Pall. and M. (Stenocranius) gregalis Pall. is changed according to the landscape zones. Collections of fleas and gamasids from the terrestrial nests are recommended to be used for studying the species composition of ectoparasites of Microtus Schr. and epizoothological examination of the territory.